Hypercyclic operators on spaces of block-symmetric analytic functions - Kravtsiv, V.V.; Mozhyrovska, Z.G.; Zagorodnyuk, A.V. (Carpathian Mathematical Publications, 2013)
The paper contains proof of the hypercyclicity of “symmetric translation” on the algebras of block-symmetric analytic functions of bounded type on an isomorphic copy of l_1.